Spatial distributions of thrips on long beans in UiTM Pahang / Mohd. Rasdi, Z. ...[et al.] - Z, Mohd. Rasdi; K, Fairuz; I, Fauziah; A.D, Hazmi; H, Hasni; B, Md. Jamaluddin (2008)
A study has been carried out to determine the population dynamics as well as the spatial distributions of thrips infesting long beans cultivation. This study was carried out at the student's share farm plot in UiTM Pahang. This study was aimed to obtain the primary data on the abundance of thrips population in of Universiti Teknologi MARA (UiTM) Pahang share farm plot and also to determine the spatial distributions of thrips on long bean. During the study, no insecticide has been applied in order to determine the abundance of thrips population naturally. Data collection started from the flowering stage till to the harvesting period. A total of 150 flowers were sampled every week for nine consecutive weeks. The population dynamics of thrips adults (P<0.01) and nymphs (P<0.01) presence in the plot were found significantly higher at the end of fruiting period. The increasing rates of adults thrips were found higher than the nymphs throughout the study. The spatial distributions of thrips in the plot were found aggregated where both variance-to-mean ratio and Morisita 's index value for thrips adults and nymphs were greater than one (index>1) in every sampling dates. Although there were some natural enemies observed in this study, their population still did not sufficient in controlling thrips infestation. The development of natural enemies in the plot seems to be slower than the thrips population.